2018
DOI: 10.12659/msm.911505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Oxalate on Expression of Clusterin and Lower Urinary Tract Symptoms in Prostatitis and Benign Prostatic Hyperplasia Patients with Calculi

Abstract: BackgroundProstatic calculi are common in urological treatments. Our major purpose in the present study was to explore the occurrence and composition of prostatic calculi, and investigate the effect of calcium oxalate (CaOx) on clusterin expression and lower urinary tract symptom (LUTS) in prostatitis and benign prostatic hyperplasia (BPH) patients with calculi.Material/MethodsFrom December 2016 to January 2017, a total of 79 prostatitis patients aged more than 50 years were enrolled. The patients were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Sun et al enrolled 79 prostatitis patients over 50 years of age, and the composition of PC in patients with LUTS was detected by quantitative realtime polymerase chain reaction, Western blotting, and immunofluorescence. Their conclusion suggested that large PC were related to LUTS, and that calcium oxalate (the main component of PC) leads to the occurrence of large PC (16). The results of Geramoutsos et al are consistent with those of Sun et al; that is, the small PC observed in elderly men were normal, but large PC were associated with chronic prostate inflammation and LUTS (26).…”
Section: Pc and Lutssupporting
confidence: 55%
See 2 more Smart Citations
“…Sun et al enrolled 79 prostatitis patients over 50 years of age, and the composition of PC in patients with LUTS was detected by quantitative realtime polymerase chain reaction, Western blotting, and immunofluorescence. Their conclusion suggested that large PC were related to LUTS, and that calcium oxalate (the main component of PC) leads to the occurrence of large PC (16). The results of Geramoutsos et al are consistent with those of Sun et al; that is, the small PC observed in elderly men were normal, but large PC were associated with chronic prostate inflammation and LUTS (26).…”
Section: Pc and Lutssupporting
confidence: 55%
“…The results of the reviewed studies suggested that type I PC may be caused by the obstruction of prostatic secretions around benign prostatic hyperplasia or occlusion caused by chronic inflammation (1), and that type II PC may be associated with urinary reflux, which leads to the formation of PC via changing local ion and pondus hydrogenii (2,9). Other studies have analyzed the chemical composition of PC and consistently reported that calcium phosphate stones were the main components of PC (16). However, there does exist an inconsistency, as calcium phosphate is not a component of prostate secretion.…”
Section: Formation Of Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…There are data both in favor and against the connection between lower urinary tract symptoms and the presence of prostate calcifications. Gross calcification of the prostate can be associated with inflammation and requires further evaluation and, if necessary, treatment of its consequences [1][2][3][4]. In clinical practice, in such a case, we diagnose chronic calculous prostatitis, which in most cases proceeds as chronic pelvic pain syndrome.…”
mentioning
confidence: 99%